2015
DOI: 10.3382/ps/pev304
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of pectoralis major myopathies in modern broiler chicken lines

Abstract: This is the first report providing estimates of the genetic basis of breast muscle myopathies (BMM) and their relationship with growth and yield in broiler chickens. In addition, this paper addresses the hypothesis that genetic selection for increase breast yield has contributed to the onset of BMM. Data were analyzed from ongoing recording of BMM within the Aviagen breeding program. This study focused on three BMM: deep pectoral myopathy (DPM; binary trait), white striping (WS; 4 categories) and wooden breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
132
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 53 publications
12
132
2
4
Order By: Relevance
“…Here, we describe three categories of WB as no, moderate and severe including reference dummies. Similar attempts have recently been presented to categorise severity of white striping (Bailey et al ., ; Trocino et al ., ), and the separate and combined occurrences of white striping and wooden breast (Mudalal et al ., ; Soglia et al ., ). It should be emphasised that the samples categorised as severe WB in this study may not be fully comparable to previous studies, as in the present study some PMs with extreme WB are discarded at the slaughter line.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe three categories of WB as no, moderate and severe including reference dummies. Similar attempts have recently been presented to categorise severity of white striping (Bailey et al ., ; Trocino et al ., ), and the separate and combined occurrences of white striping and wooden breast (Mudalal et al ., ; Soglia et al ., ). It should be emphasised that the samples categorised as severe WB in this study may not be fully comparable to previous studies, as in the present study some PMs with extreme WB are discarded at the slaughter line.…”
Section: Discussionmentioning
confidence: 99%
“…White striping (WS) is one of the most important emerging problems for the poultry industry, and its appearance, particularly in breast meat, has been rapidly increasing (Bailey, Watson, Bilgili, & Avendano, ; Kuttappan, Hargis, & Owens, ; Petracci et al, ). White striping (WS), the quantity and thickness of which changes from bird to bird, is characterized by white parallel lines in the same direction of the muscle fibres.…”
Section: Introductionmentioning
confidence: 99%
“…However, a new type of myopathy, referred to as "white striping" or "wooden breast", which occurs without nutritional deficiencies or infectious diseases and only in the pectoralis major muscles of commercial broiler chickens has frequently been reported in recent years in the worldwide broiler industry (Sihvo et al, 2014;Velleman and Clark 2015). The white striping is characterized by visible white lines parallel to the direction of the muscle fibers, while the wooden breast is characterized by hardening and an exudate of the breast muscle (Bailey et al, 2015). However, the difference in pathogenesis between the two phenotypes has not been strictly classified.…”
Section: Discussionmentioning
confidence: 99%
“…Pale-colored exudative meat has been found in both broiler chickens and turkeys (Woelfel et al, 2002;Owens et al, 2009;Bailey et al, 2015;Velleman and Clark 2015). Smith and Northcutt (2009) reported that this pale-colored exudative avian muscle differed from pale, soft, and exudative porcine meat.…”
Section: Introductionmentioning
confidence: 99%